Identification of Sarcocystis spp. in synanthropic (Muridae) and wild (Cricetidae) rodents from Argentina - Bentancourt Rossoli, Judith Victoria (2024)
The occurrence of Sarcocystis species was investigated in synanthropic (Muridae) and wild (Cricetidae) rodents from Argentina. Nine species were captured (n = 356). Sarcocysts were detected in muscles of 8.7% (31/356) and 3.7% (4/106) of the rodents by histopathology and direct microscopic observation, respectively. PCR-sequencing targeting the 18S rRNA, cox1, and ITS1 regions was performed on samples with positive histopathology. Four different 18S rRNA sequences or sequence groups with high intra-group identities (99.6–100%) were detected in Mus musculus, Oxymycterus rufus, Akodon azarae, and Necromys lasiurus. Eight sequences showed 99.5–99.7% identity with S. dispersa. Thirteen sequences showed low identity (95.3–96.4%) with other Sarcocystis spp. The obtained coxI sequences (n = 9) were almost identical to each other and showed a high similarity with S. strixi (99.2–99.5%) and S. lutrae (99.1%), despite the 18S rRNA sequences from the same samples suggested the occurrence of at least two species. This suggests that coxI may not show high variability in Sarcocystis spp. that use rodents as intermediate hosts. Six ITS1 sequences were obtained, showing high identity but low coverage with several Sarcocystis spp. Multilocus sequence typing and BLAST analysis did not lead to an accurate species identification. Possible reasons are the detection of new species or the limited molecular information available from previously described Sarcocystis spp. Phylogeny suggests that the detected Sarcocystis spp. may use raptor birds or snakes as definitive hosts. This study represents the first molecular identification of Sarcocystis spp. in naturally infected rodents of the Cricetidae and Muridae families in South America.